Studia nad pamięcią a archeologia późnego paleolitu. O performatywnym wymiarze praktyk pamięci w pradziejowych społecznościach łowiecko-zbierackich - Mugaj, Jakub (Folia Praehistorica Posnaniensia, 2019)
The researches on the Paleolithic society of hunters-gatherers enter into an inspiring perspective, enriching the reflection on memory. The article considers the forms of the collective memory of the hunters-gatherers community of the Paleolithic era. The author postulates to widen the term of memory with the practices of embodiment and habitual memory. It helps to grasp the ways of memorizing by the communities on a deeper level. Cultural memory is deeply rooted in routine activities, which is more or less conscious. The mnemotechnic power that lives in such activities allows for preserving of cultural models. The archaeological analyses of flint working materials present the very concrete examples of such events.